Validity of the ‘Dunya Hejo (Du-Jo)’ Problem-Based Learning E-Worksheet on Climate Change and Global Warming - Devi Yulianty Surya Atmaja; Achmad Samsudin (CV FOUNDAE, 2024)
Climate change and global warming are critical environmental issues that require effective educational strategies to enhance students' understanding. Student worksheets can play a significant role in facilitating active learning on these topics. This research aims to determine and describe the validity of the